A comparison of peri-operative outcomes between elective and non-elective total hip arthroplasties - Anis, Hiba K.; Sodhi, Nipun; Coste, Marine; Ehiorobo, Joseph O.; Newman, Jared M.; Garbarino, Luke J.; Gold, Peter; Freund, Benjamin; Piuzzi, Nicolas; Mont, Michael A. (Annals of Translational Medicine; Vol 7, No 4 (February 27, 2019): Annals of Translational Medicine (Focus on “Lower Extremity Arthroplasty”), 2019)
Background: Elective total hip arthroplasties (THAs) entail a more extensive pre-operative planning process compared to non-elective THAs and this may contribute to a disparity in outcomes. However, the differences in peri- and post-operative outcomes between elective and non-elective THAs remain unclear. Therefore, the purpose of this study was to: (I) determine nationwide trends in operative times and (II) evaluate the association between surgery type, elective or non-elective with respect to (I) operative times; (II) hospital lengths-of-stay (LOS); (III) discharge disposition; (IV) 30-day post-operative complications; (V) reoperations; and (VI) readmissions. Methods: The NSQIP database was queried for all primary THAs (CPT code 27130) performed between 2011 and 2016. This yielded 130,261 cases, which were then stratified into elective (n=125,293) and non-elective (n=4,968) cases. One-way analysis of variance (ANOVA) were used to evaluate the associations between operative times and surgery year. Univariate analyses of surgery type with the following outcomes of interest were also performed: operative times, LOS, and discharge disposition as well as 30-day complication, reoperation, and readmission rates. A multiple linear regression model was used to evaluate the relationships of operative times and LOS with surgery types after adjusting for surgery year and patient factors [age, sex, body mass index (BMI), and American Society of Anesthesiologists (ASA) score]. A log-transformed dependent variable was used to calculate the percentage difference in mean operative times and LOS. Multivariate logistic regression models adjusted for patient factors and year of surgery were used to evaluate associations of surgery type with complication, reoperation, and readmission rates. Results: Over the 6-year period, mean operative times (93 vs. 103 minutes, P